Urban infrastructure issues and concerns - Pathania, Mamta (2011)
Infrastructure development is of great importance today. A robust infrastructure triggers rapid development and contributes to the process of poverty alleviation. As the world's population grows, improving living standards without destroying the environment is a global challenge. Given the increasing pace of urbanizationin the less developed region in the next 15 years, it is high time to gear up to meet its challenges - good governance and good living environment with better access to civic services. From water and sewer systems to road and rail networks to the national power and natural gas grids, infrastructure includes everything which is required for modernising the fundamental structures that support the civilisation. The problem with regard to infrastructure is particularly acute in urban areas, where growing population stress society's support systems, and natural disasters, accidents, and terrorist attacks threaten infrastructure safety and security. This article presents a systematic analysis of the theory and practice of urban infrastructure management. It makes an attempt to bring together theoretical and practical experiences to understand the economic, social and financial aspects of urban infrastructure management. Describing the various initiatives at the government level this article tries to portray the road ahead for all round infrastructure development of India. - Reproduced.
Keywords: Urbanization